Epistaxis in Visceral Leishmaniasis: A hospital based study in Eastern Nepal - Sigdel, B; Bhandary, S; Karki, P; Ghimire, A (International Journal of Infection and Microbiology, 2012)
INTRODUCTION: Epistaxis is a common clinical manifestation in endemic areas of Visceral Leishmaniasis (VL). This study aims to see the prevalence of epistaxis in VL in Eastern Nepal. MATERIALS AND METHODS: This study was a prospective cross sectional hospital based study. Diagnosis was made by Rk-39 from peripheral smear & Leishmania donovani (LD) bodies from bone marrow. Before starting anti–kalaazar treatment, nasal examination findings were noted. RESULTS: Ninenteen out of 80 diagnosed case of VL patients had epistaxis (23.8%) with age group between 7-66 years. One patient had developed severe epistaxis and hemotoma and died. CONCLUSION: Epistaxis is a common ent finding in endemic area of VL, however this needs to be confirm with larger cohorts. DOI: http://dx.doi.org/10.3126/ijim.v1i1.6942 Int J Infect Microbiol 2012;1(1):38-40